2010
DOI: 10.1152/ajprenal.00075.2010
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of serum and glucocorticoid-regulated kinase 2 in the regulation of Na+/H+exchanger 3 in the mammalian kidney

Abstract: Serum and glucocorticoid-regulated kinase 2 (sgk2) is 80% identical to the kinase domain of sgk1, an important mediator of mineralocorticoid-regulated sodium (Na(+)) transport in the distal nephron of the kidney. The expression pattern and role in renal function of sgk2 are virtually uncharacterized. In situ hybridization and immunohistochemistry of rodent kidney coupled with real-time RT-PCR of microdissected rat kidney tubules showed robust sgk2 expression in the proximal straight tubule and thick ascending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 65 publications
0
36
0
1
Order By: Relevance
“…Thus, whether ENaC is selectively regulated by SGK1, or whether other signaling molecules can also regulate ENaC in a physiologically relevant manner, becomes a question of considerable importance. There have been conflicting reports based on cell culture and oocyte studies regarding the roles of several SGK1 relatives (31,32,(44)(45)(46). Furthermore, there have been conflicting reports regarding the effects of SGK1 on transporters other than ENaC.…”
Section: 4mentioning
confidence: 99%
“…Thus, whether ENaC is selectively regulated by SGK1, or whether other signaling molecules can also regulate ENaC in a physiologically relevant manner, becomes a question of considerable importance. There have been conflicting reports based on cell culture and oocyte studies regarding the roles of several SGK1 relatives (31,32,(44)(45)(46). Furthermore, there have been conflicting reports regarding the effects of SGK1 on transporters other than ENaC.…”
Section: 4mentioning
confidence: 99%
“…Unlike Sgk-2, which is not reported to interact with NHERF2 effective regulation of NHE3 by Sgk-1 requires NHERF2 [20]. The OKP cells used in the Sgk-2 study are not reported to express adequate levels of endogenous NHERF2 [43] hence the lack of effect of Sgk-1 that these investigators observed may be simply due to the absence of NHERF2.…”
Section: Discussionmentioning
confidence: 91%
“…Conversely, the absence of Sgk-1 can be protective as shown in studies using DOCA/high salt treated mice where glomerulosclerosis and tubulointerstitial fibrosis was blunted in Sgk-1 -/-mice compared to wild type controls [51]. Sgk-2 is also expressed in the proximal tubule and a recent study showed that overexpression of constitutively active Sgk-2 in OKP cells increased NHE3 activity but were unable to demonstrate any effect with Sgk-1 [43]. Unlike Sgk-2, which is not reported to interact with NHERF2 effective regulation of NHE3 by Sgk-1 requires NHERF2 [20].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Reactions were amplified using the Applied Biosystems Prism 7900HT Fast Real-Time PCR system. Results were expressed as 2 Ϫ⌬⌬Ct values, with ⌬Ct ϭ CtmiR Ϫ Ctsno202 (29). Expression of miR-466g was normalized to expression of the control miRNA sno-202.…”
Section: Methodsmentioning
confidence: 99%